Melatonin enhances sorafenib-induced cytotoxicity in FLT3-ITD acute myeloid leukemia cells by redox modification - Tian, Tian (Theranostics, 2019)
Acute myeloid leukemia (AML) with an internal tandem duplication in Fms-related tyrosine kinase 3 (FLT3-ITD) is identified as a subgroup with poor outcome and intrinsic resistance to chemotherapy and therefore urgent need for development of novel therapeutic strategies. Methods: The antitumor effects of melatonin alone or combined with sorafenib were evaluated via flow cytometry and immunoblotting assays in FLT-ITD AML cells. Also, the ex vivo and in vivo models were used to test the synergistic effects of melatonin and sorafenib against leukemia with FLT3/ITD mutation. Results: Our study shows for the first time that melatonin inhibits proliferation and induces apoptosis in FLT3/ITD-positive leukemia cells. Mechanistically, melatonin preferentially causes overproduction of reactive oxygen species (ROS) and ultimately massive cell death in FLT3-ITD AML cells. Moreover, melatonin significantly enhances the cytotoxicity induced by the FLT3 tyrosine kinase inhibitor sorafenib in AML cells with FLT3/ITD through redox modification. Importantly, combination of melatonin and sorafenib exhibited highly synergistic therapeutic activity in MV4-11 xenografts and a murine model bearing FLT3/ITD leukemia. Conclusion: This study indicates that melatonin, alone or in combination with sorafenib, has potential to improve the therapeutic outcome of AML patients with FLT3-ITD mutation that merits further investigation.